IMKĀNIYĀT AL-IJTIHĀD AL-ISTIṢLĀHĪ WA ISHĀMĀTUHU LI HALL AL-QADHĀYĀ AL-FIQHIYYAH AL-MU’ĀṢARAH: DIRĀSAT FĪ FATĀWĀ JĀ’IHAH COVID FĪ INDONESIA - Sa’dan, Saifuddin; Mubarrak, Husni; Hamdiah, Hamdiah; Kjoor, Amir Muhammed Kafei (Universitas Islam Negeri Ar-Raniry, 2024)
This article would like to discuss one of the theories of ijtihād that is well-recognized in the science of ushūl fiqh, namely the theory of ijtihād istiṣlāhiy, in terms of its concept and its application to solve contemporary Islamic law by making the fatwas of the Covid-19 in Indonesia as the object of study. Even though a fatwa is a legal notification which is legal and unbinding, fatwa is certainly not produced from a vacuum, but has gone through a process of understanding the details of the proposed Islamic law issue and studying it using the appropriate ijtihād method, one of which is ijtihād istiṣlāhiy. This article presents the results of a qualitative research using a bibliographical study as the method. This article attempts to present an academic discussion regarding the flexibility of ijtihād istiṣlāhiy, its limits as well as its dhawābith in answering contemporary Islamic law issues by examining the side of the establishment of the Covid-19 fatwas law in Indonesia in this recent period. The results of the study show that the fatwas regarding Covid-19 in Indonesia is based on the principle of benefit (maṣlahah) reached through the ijtihād istiṣlāhiy method.